DENDROBIUM TINUKARIENSIS, A NEW SPECIES OF SECTION CALYPTROCHILUS FROM THE MEKONGGA MOUNTAINS, SOUTHEAST SULAWESI, INDONESIA - Diah Sulistiarini; Daniel Potter; Peter O'Byrne (Research Center for Biology, 2017)
SULISTIARINI, D., POTTER, D. & O’BYRNE, P. 2017. Dendrobium tinukariensis, a new species of section Calyptrochilus from Mekongga Mountains, South East Sulawesi, Indonesia. Reinwardtia 16 (2): 103–106. — A new species of Dendrobium (Orchidaceae), D. tinukariensis is described and illustrated from Mekongga, Southeast Sulawesi, Indonesia. It belongs in Dendrobium sect. Calyptrochilus.